Effect of boron toxicity on pollen tube cell wall architecture and the relationship of cell wall components of Castanea mollissima Blume - Zhang, Weiwei; Zhang, Qing; Xing, Yu; Cao, Qingqin; Qin, Ling; Fang, Kefeng (Frontiers in Plant Science, 2022)
Boron (B) is essential to plant development. However, excessive B is toxic to plants. This research was performed to evaluate the effects of B toxicity on cell wall architecture of Chinese chestnut (Castanea mollissima Blume) pollen tubes with emphasis on the relationship among pectins, cellulose, and callose. Results showed that 0.8 mM H3BO3 inhibited pollen germination and led to abnormal morphology of the pollen tubes. B toxicity also affected the distribution of cell wall components of the pollen tube. In control pollen tube, esterified and acid pectins were distributed unevenly, with the former mainly at the tip and the latter on the distal region. Cellulose was distributed uniformly on the surface with less at the tip; callose reduced gradually from base to sub-tip of the pollen tubes and no callose at the tip of the tube was detected. B toxicity led to the deposition of esterified and acid pectins, cellulose, and callose at the tip of the pollen tube. Results from scanning electron microscopy and transmission electron microscopy showed that B toxicity also altered pollen tube wall ultrastructure. The results from enzymatic treatment illustrated that there existed a close relationship among pectins, cellulose, and callose. B toxicity also altered the relationship. In a word, B toxicity altered deposition and relationship of pectins, cellulose, and callose of pollen tube wall.